Operation Study of the Node of Stringer Staged Connection Point of the Railway Bridge Track-Way - Kliuchnyk, S. V (Science and Transport Progress, 2021)
Purpose. The staged connections of the stringers of railway bridge track-way have the simplest design, but some design flaws result in numerous defects. The purpose of this work is an investigation of the previously proposed methods of strengthening the support node for the stringers of the track-way of a staged communication, as well as investigation of the work of the reinforcement proposed by the author. Methodology. The author analyzes the condition of metal bridges operated on the railway. It was found that the decisive element in determining the load capacity of the entire bridge are the stringers of the track-way. To achieve this goal, the author analyzed the stress-strain state of the support node of the stringer on the cross-bar without and with reinforcement using the finite element method. The discovered rational parameters of the proposed reinforcement unit. The calculations were performed in Selena software. Findings. Stress-strain state of the connection point of the stringers with the floor beamsnode on condition of their staged position was obtained and analyzed. The author selected the rational parameters of the reinforcement elements of the stringer support node for the staged communication and analyzed stress-strain state of the new connection node of the stringers with the floor beams at their staged location based on typical spans of Proiektstalkonstruktsii LLC (PSK). The analysis shows that after the proposed reinforcement, the maximum stresses in the horizontal legs of the flange angles of the stringers and floor beams, which destroyed the structures, decreased by 43–73%. Originality. The work analyzes the stress-strain state of metal stringers of the track-way of the staged location taking into account the joint work of stringers with load-bearing trusses, as well as the stress-strain state of the proposed reinforcement of the support node of metal stringers with the identification of rational parameters. Practical value. This method of repair with reinforcement is recommended as the most rational for a bridge over the Inhulets river at 109 km of the Verkhivtseve – Dolynska Railway (contract No. 94/2011–TsTekh–177/2011–ETU dated 09/30/2011). Based on these results, a patent for utility model No. 109806 dated 09/12/2016 was issued.